Breast cancer anti-hormonal therapy and rheumatic diseases: linking the clinical to molecular world - Nadia Melillo; Francesco Paolo Cantatore (Verduci Editore, 2020)
Anti-hormonal therapies are used in the treatment of hormone dependent breast cancer. Their use may be complicated with the onset of arthralgia and autoimmune diseases. Recently a clinical relationship between oestrogen, anti-oestrogen therapy and rheumatic diseases has been reported in the literature, but, until now, experimental supporting data about the interacting biochemical pathways involved are still very limited. The understanding of this molecular link may provide important information to elucidate the relationship between autoimmunity and cancer mechanism and treatment. This review is intended to highlight the relationship between known common molecular mechanisms which explain this association and that probably need to be investigated in future studies.